P 79 Physiological assessment of the sense of agency in psychogenic movement disorders. Issue 10 (October 2017) - Henn, P.; Duesmann, C.; Fricke, C.; Classen, J.
Abstract : Psychogenic movement disorders (PMD) are conditions characterized by the occurrence of unwanted motoric symptoms in which a somatic reason cannot be found. As patients suffering from PMD experience their pathological movements as non-voluntary, it is hypothesized that those patients have an altered sense of agency (SoA). SoA is defined as the feeling of controlling ones own actions and through them controlling events in the external world (Haggard and Tsakiris, 2009 ). SoA can be assessed by measuring the intentional binding (IB) effect. This is the perceived convergence of the time between a voluntary action and an auditory stimulus provoked by that action. To test the hypothesis we used a setting based on the Libet clock method (Libet et al., 1983 ) introduced byHaggard et al. (2002) . To date, in total 59 subjects were enrolled: 5 subjects with the diagnosis of PMD, 35 with a somatic movement disorder (SMD) and 19 healthy controls. SMD patient group consisted of patients with Parkinsons disease ( n  = 18), neuropathies ( n  = 10), stroke ( n  = 7) and multiple sclerosis ( n  = 1). IB values were 0.18 ± 0.06 s for PMD, 0.16 ± 0.09 s for SMD and 0.12 ± 0.09 s for healthy controls (mean ± SD). So far, there were no significant differences in IB between PMD, SMD and healthy controls in the examined study group (PMD vs. healthy controls, p  = 0.1. Two-sample t -tests). Patients with a motor disorder (both SMD and PMD) tended to have higher IB values compared to healthy controls (SMD vs. healthy controls, p  = 0.08). IB values did not differ between SMD and PMD patients (PMD vs. SMD, p  = 0.7). Our findings are in line with evidence derived from small study groups that binding processes are altered in PMD patients compared to healthy controls (Kranick et al., 2013 ). However, since PMD patients did not differ from SMD patients, a specific binding problem is unlikely to represent the pathophysiological mechanism in psychogenic movement disorders.